"WE NEED RADICAL GAMEPLAY, NOT JUST RADICAL GRAPHICS": TOWARDS A CONTEMPORARY MINOR PRACTICE IN COMPUTER GAMING. - Franklin, Seb (symplokē, 2009)
The article offers information on the practice of computer programmers to rework source codes of computer games. It presents the advantage of using Genetic Lifeform and Disk Operating System (GLaDOS) to enhance computer stability which is the most basic requirement of gameplay. It highlights the video game "Portal" which uses coded space in the gaming process.